Expanding Sustainable Land Governance: A Geospatial Framework for Incorporating Natural Parks into Urban Cadastres—Lessons from Darke de Mattos Park, Rio de Janeiro - Auzenan Pereira de Sá; Andrew Santana da Silva; Leonardo Vieira Barbalho; Jorge Luís Nunes e Silva Brito; Andrea Galudht Santacruz Jaramillo; Sonia Maria Lima Silva; Luiz Carlos Teixeira Coelho (Land, 2025)
Contemporary metropolises, particularly those in the Global South, grapple with the complex challenge of balancing urban development with environmental conservation. In such contexts, forest remnants often face constant threats from illegal urban encroachment and insufficiently defined boundaries, which undermine conservation efforts and hinder effective legal enforcement. This study explores cost-efficient, geographic-information-technology-driven solutions to improve the management of conservation units and incorporate them into cities’ multipurpose land cadastres. By employing tools such as a remotely piloted aircraft, total stations, and GNSS receivers, this work highlights the pivotal role of geotechnologies in safeguarding the urban natural heritage. These technologies not only address the pressures of urban expansion but also enable continuous monitoring and impact assessment through geographical information systems (GISs). To illustrate these applications, this study examines a case study from Rio de Janeiro, Brazil, the Darke de Mattos Municipal Park, to demonstrate how accurate geographic data can significantly enhance planning and management efforts while maintaining cost-effectiveness.